2010
DOI: 10.2478/s11696-010-0062-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lead dioxide electrodes morphology on kinetics and current efficiency of oxygen-ozone evolution reactions

Abstract: Influence of electrode morphology on electrochemical properties of lead dioxide electrodes (β-PbO2) for oxygen-ozone evolution reactions in acid medium was investigated using scanning electronic microscopy (SEM), cyclic voltammetry (CV), polarization curves (PC), and determination of the current efficiency (Φ). Experimental findings revealed that application of high electrodeposition current densities furnishes more rough β-PbO2 films. Surface characteristics were verified by SEM images and the analysis of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Hence current density cannot be the only factor governing current efficiency. This in agreement with Rufino et al 68 and Da Silva et al 69 who reported that ozone current efficiency is affected by temperature, real current density (i.e taking into account electrochemically active surface area), electrode and electrolyte composition.…”
Section: Table I Assignments and Relative Peak Intensities Of The Var...supporting
confidence: 91%
“…Hence current density cannot be the only factor governing current efficiency. This in agreement with Rufino et al 68 and Da Silva et al 69 who reported that ozone current efficiency is affected by temperature, real current density (i.e taking into account electrochemically active surface area), electrode and electrolyte composition.…”
Section: Table I Assignments and Relative Peak Intensities Of The Var...supporting
confidence: 91%
“…4) with a lower redox potential. Because of that, to promote the formation of the triatomic molecule, strategies such as working with electrodes exhibiting high anodic overpotential for the oxygen evolution reaction [30][31][32][33] or applying rather large current densities should be applied.…”
Section: Fundamentals Of Electrochemical Ozone Generationmentioning
confidence: 99%
“…However, the competition between oxygen and ozone generation was found to be a problem and, to overcome it, fluoroanions additions were found to enhance the ozone formation, although this improvement was not found to be totally viable because these species are generally toxic to human beings and harmful to the environment [60]. In addition, the leakage of toxic lead ion to the aqueous phase during the use of lead dioxide coatings was also found to be a significant problem and many efforts were made trying to avoid using different manufacturing procedures and formulations of the coatings [32,39,41,44,[62][63][64]. In addition, the doping of a PbO2-based electrode with certain ions such as, Bi 3 + , Fe 3+ , Со 2+ , and Fwas found to considerably increases its electrocatalytic activity in the formation of hydroxyl radicals, which are the precursors of either О3 synthesis or enhanced the oxidation of substances contaminants.…”
Section: Equipment For the Electrolytic Production Of Ozonementioning
confidence: 99%
“…exhibit two linear regions distributed in the low and high values of the scan rate, i.e. two distinct pseudocapacitances can be found for solid electrodes [56,59,66]. This experimental fact can be understood from the theoretical viewpoint by taking into account that the total pseudocapacitive current density (j c,T ) for electrodes containing surface defects is composed of contributions from the 'inner/internal' and 'outer/external' surface regions [59]:…”
Section: Inner and Outer Surface Areas Of The Mome-nico 2 O 4 Electrode And The Electrochemical Porositymentioning
confidence: 99%